Distribution of white spot lesions among orthodontic patients attending teaching institutes in Khartoum - Maha Kamal Eltayeb; Yahia Eltayeb Ibrahim; Ikhlas Ali El Karim; Nada Mirghani Sanhouri (BMC, 2017)
Abstract Background Fixed orthodontic appliances render teeth cleaning arduous, thus when orthodontic treatment is associated with inadequate oral hygiene practice, development of white spot lesions (WSLs) imposes a significant risk on the dentition. Salivary reservoir of calcium, magnesium, phosphorous and fluoride counteracts demineralization and encourages remineralization providing protection against caries challenge. The investigation of the factors leading to WSLs' development is mandatory for appropriate prevention strategies planning. The present study aimed at evaluating the prevalence, pattern of distribution and contributing factors to WSLs' development, among orthodontic patients attending orthodontic departments in teaching institutes in Khartoum. Methods This cross-sectional descriptive, analytical clinical based study was carried out among fixed orthodontic patients attending teaching institutes in Khartoum State. All patients visiting the clinics for their follow up during a 3 months period and fulfilling the inclusion criteria were included. The International Caries Detection and Assessment System (ICDAS) served as a guide for standardized visual caries assessment. Saliva samples were collected from a sample of patients and the levels of calcium and phosphorus were measured. Patients were interviewed regarding their oral hygiene habits (frequency of tooth brushing, use of interdental brushes and mouth washes). Frequency distribution tables as well as graphs, Pearson's correlations and Spearman's correlation were used in the statistical analysis. Results The overall prevalence of WSLs was 61.4%. The prevalence for each tooth was: 48.1% in the canine, 32.3% in the lateral incisor, 31.6% in both the central incisor and the first premolar, 27.2% in the second premolar and 8.9% in the first molar. No significant relationship between WSLs prevalence, age and gender or oral hygiene measures was found. There was no significant difference in calcium and phosphorus level between participants with WSLs or those with sound teeth (p-values for calcium and phosphorus were 0.154 and 0.567 respectively). Conclusions Within the limitations of this study it was found that WSLs among fixed orthodontic patients represented an issue of concern. High prevalence of WSLs was recorded among orthodontic patients in Sudan, indicating a need for more stringent prevention programmes and oral hygiene practices prior to initiation of orthodontic treatment.